The Diagnosis and Management of Asherman’s Syndrome Developed after Cesarean Section and Reproductive Outcome - Pinar Ozcan Cenksoy; Cem Ficicioglu; Mert Yesiladali; Ozge Kizilkale (Case Reports in Obstetrics and Gynecology)
Intrauterine adhesions (IUAs) frequently occur as a result of trauma to the basal layer of endometrium following pregnancy-related curettage such as incomplete abortion (33,3%), postpartum hemorrhage (37,5%), and elective abortion (8,3%). Hysterotomy, myomectomy, Cesarean section, hysteroscopic procedures, such as resection of submucosal leiomyomata or uterine septae, and endometrial ablation are less common etiologic factors resulting in IUA formation. Patients with Asherman’s syndrome usually present with menstrual disturbances, infertility, or recurrent pregnancy loss. A successful treatment of infertility could be achieved by restoration of the uterine cavity, prevention of IUA reformation, and promotion of healing process. We presented the diagnosis and management of a case that suffers from menstrual disturbances and secondary infertility resulted from IUA formation developed after Cesarean section.